ID 299 – Retinal involvement in fronto-temporal dementia: Role of optical coherence tomography and clinical implications. Issue 3 (March 2016) - Ferrari, L.; Coppi, E.; Vitali, F.; Magnani, G.; Comi, G.; Leocani, L.
Abstract : Objectives: Frontotemporal dementia (FTD) is a clinical syndrome subtending a neurodegenerative process that involves mainly fronto-temporal lobes. Optical coherence tomography (OCT) provides high-resolution images of retinal nerve fiber layer (RNFL). Retinal neurodegeneration has been described in carriers of progranulin mutations. We aimed to investigate RNFL thickness in FTD subjects compared to healthy controls (HC), also considering clinical-neuropsychological aspects. Methods: Ten FTD subjects (65 ± 7 y.o.) and 49 HC (68 ± 7 y.o.) underwent spectral domain OCT. The two groups were compared through T -test, then correlation between RNFL and age at OCT examination, disease duration, mini-mental state examination, proteins tau, phosphorylated-tau and amyloid-beta 1–42 was done through Pearson test. Results: RNFL was significantly reduced at global, superior and inferior quadrant, in FTD compared to HC ( p  = 0.05): average 89.60 ± 4.95 mm vs. 98.37 ± 7.46 mm; superior 111.20 ± 10.62 mm vs. 121.06 ± 11.55 mm; inferior 112.40 ± 9.93 mm vs. 125.22 ± 12.35 mm. FTD subjects RNFL inversely correlated with disease duration. No significant correlations appeared with clinical-neuropsychological data. Conclusions: Our data confirm RNFL involvement in FTD. Future studies will be needed to further explore neuropsychological and biomarkers correlations and to define the value of OCT as a rapid and high reproducible tool to monitor FTD evolution.